Evaluation of the deterioration in Brazil nut seeds by the tetrazolium test - Camargo, Ivo Pereira de; Carvalho, Maria Laene Moreira de; Vieira, Maria das Graças Guimarães Carvalho (Pesquisa Agropecuaria Brasileira, 1997)
The objective of this work was to establish coloration patterns by the tetrazolium test that allows evaluation of the physiological quality of the Brazilian nut seeds (Bertholletia excelsa Humb. & Bompl.). After 30 days of storage in laboratory environmental conditions, and thereafter, every 15 days, at amount of 105 days, the moisture content and the coloration patterns in the internal sections of kernels were evaluated. With the storage time there was a decrease in the moisture content and in the percentage of the kernels with pink color and an increase in the percentage of kernel with white blots. The white coloration tended do fill up all the internal sections of the kernel indicating that there is possibly an association with the evolution of water loss and deterioration of the seeds.